Pengaruh Senam Hamil Terhadap Kualitas Tidur Ibu Hamil Trimester III di PMB Ida Laina Kota Bengkulu Tahun 2025 - Heni Dyah Aprianti; Tuti Rohani; Ronalen Br. Situmorang (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The third trimester of pregnancy is a critical period marked by various physiological changes, such as uterine enlargement, increased urinary frequency, back pain, and sleep disturbances. One of the most common sleep disturbances is insomnia, which is influenced by anxiety, changes in body posture, and psychological stress leading up to childbirth. According to WHO data, the global prevalence of insomnia among pregnant women reaches 41.8%, and in Indonesia, 75% of pregnant women experience a decline in sleep quality. This study aims to determine the effect of prenatal exercise on sleep quality among third-trimester pregnant women at the Ida Laina Maternity Clinic in Bengkulu City. It is a pre-experimental study with a pre-test and post-test, single-group design, using a questionnaire and an observation sheet as measurement tools. Based on the results of statistical analysis using the Wilcoxon Signed Rank Test, it was found that 18 (100%) pregnant women experienced sleep disturbances before participating in prenatal exercise, and 13 (72.2%) pregnant women experienced improved sleep quality after participating in prenatal exercise (negative ranks), 5 pregnant women showed no change (ties), and no pregnant women experienced a decrease in sleep quality (positive ranks = 0). A p-value of 0.000 indicates that there is a statistically significant difference in sleep quality before and after prenatal exercise. Thus, it can be concluded that prenatal exercise has a significant effect on improving sleep quality in pregnant women in the third trimester. The results of this study can be used as a basis for designing more effective educational or counseling programs on the benefits of prenatal exercise.